The Symbol of Beauty viewed From George Gordon Byron's Poem "She Walks in Beauty" - Nurbaiti Ali Nasution (International Journal of English and Applied Linguistics (IJEAL), 2022)
The symbol of beauty viewed from George Gordon Byron's poem, entitled She Walks in Beauty, shows a high imagination of George Gordon Byron about beauty, especially in physical and inner beauty. This research exposes the character of a woman who keeps her beauty with her excellent character. The poet expresses a beautiful woman's beauty and good traits. Her beauty in the poem symbolizes many things, for instance, serenity, peace and goodness. The woman is described as a figure who has exceptional beauty in herself. She uses her beauty without arrogance. The woman is the superior woman who can balance her physical and inner beauty. So, a remarkable woman can show good character or attitude to others.